Discovery of Novel Anthranilic Diamide Derivatives Bearing Sulfoximine Group as Potent Insecticide Candidates - Zhang, Hongyuan; Peng, Jinmin; Zhong, Yuanhan; Chen, Yue; Wang, Qing; Hadiatullah, Haditullah; Xie, Weibin; Xiong, Lixia; Yuchi, Zhiguang; Liu, Jingbo; Li, Yuxin (Chemical research in Chinese universities, 2024)
The fall armyworm, Spodoptera frugiperda ( S. frugiperda ), represents the most resistant insect species and poses serious threat to grain yield. Chlorantraniliprole (CHL), which targets the ryanodine receptors (RyRs) in insects, has demonstrated the efficacy in controlling S. frugiperda . Nevertheless, this has led to emerging resistance in several countries. To counter this resistance, a viable approach involves the development of novel compounds that bind against RyRs via distinct binding sites or modes. In this study, a series of 22 novel anthranilic diamide derivatives was designed and synthesized, and their insecticidal activities were evaluated. Most of these derivatives showed moderate to good insecticidal activity against S. frugiperda and Mythimna separata . Time-lapse fluorescence measurements of endoplasmic reticulum luminal calcium revealed that most derivatives elicited cellular responses similar as CHL when assessed on HEK293 cells expressing S. frugiperda ryanodine receptors ( Sf RyRs). The mode of action of compound 13 a was studied and verified on the isolated neurons by calcium imaging technique. Finally, molecular docking analysis was employed to predict the binding mechanism of compound 13 a against Sf RyRs. Overall, these novel diamide derivatives hold promise as a valuable resource for guiding the future design of insecticidal compounds targeting RyRs.